Changes and processes along the Kuala Terengganu coastline during the Northeast Monsoon and other times of the year - Rosnan, Yaacob (university of Malaya, 2011)
A knowledge of coastal processes is necessary for complete understanding of the depositional or erosional framework of any coastline. The main aim of this study is to identify the processes that operate along the Northeast Monsoon influenced coastline of Kuala Terengganu. Beach profiles have been surveyed, and sediment samples collected, at different time intervals at several locations along the said coastline. During the Northeast Monsoon, the coastline is influenced by strong waves and currents, though during the rest of the year, it is subject to moderate and low hydraulic energy levels with relatively weak waves and currents.